Diverse Profiles of Toll-Like Receptors 2, 4, 7, and 9 mRNA in Peripheral Blood and Biopsy Specimens of Patients with Celiac Disease - Haniye Ghasiyari; Mohammad Rostami-Nejad; Davar Amani; Kamran Rostami; Mohamad Amin Pourhoseingholi; Hamid Asadzadeh-Aghdaei; Mohammad Reza Zali (Journal of Immunology Research)
Background and Aims. Both adaptive and innate immunity are involved in the development of celiac disease (CD). Altered Toll-like receptors (TLR) expression and activation may be partially responsible for the inflammation and subsequently crypt hyperplasia, but the main driver for inflammation is gliadin-reactive T-cells. Therefore, the aim of this study was to investigate the TLRs 2, 4, 7, and 9 gene expressions in both peripheral blood and intestinal mucosa of patients with celiac disease compared to healthy control (HC). Material and Methods. Blood samples from 120 confirmed active CD patients and 120 age- and sex-matched healthy volunteers served as control group were collected during 2015-2016. Also, 20 biopsy specimens from the study group were randomly collected. Total RNA was isolated using a standard commercial kit. The mRNA expression of TLRs was quantified by relative qPCR with β2 microglobulin (β2m) as a reference gene. Results. TLR4 (P=0.01) and TLR9 (P=0.02) mRNA were significantly elevated in blood samples from CD patients compared to the healthy controls. Moreover, TLR2 (P=0.03) and TLR4 (P=0.0003) expression level was increased in CD biopsy specimens compared to controls, whereas expression of TLR9 mRNA was significantly decreased in CD patients. There was no significant difference in the expression of TLR7 in biopsy and blood specimens. Conclusions. The alteration of TLR4 and TLR9 expression in the blood and biopsy samples of patients with CD supports the critical role of the innate immune system in the pathogenesis of this disease. Upregulation of TLR4 and TLR9 suggests the contribution of gut microbiota or dysregulation of the immune response to commensal flora in small bowel mucosa in celiac patients.